Outcome of myeloma patients with COVID5 19 on active lenalidomide-based therapy: 6 Does lenalidomide protect from severe 7 COVID-19? (2020)
Patients with haematological cancers and concurrent coronavirus disease 2019 (COVID-19) reportedly have poor outcomes as indicated by high hospitalisation rates, high case fatality rates in mechanically ventilated patients, and a high mortality rate of ≥10% [1], [2], [3]. A recent small study reported a high mortality rate among patients with myeloma and concurrent COVID-19 infection [4]. Interestingly, one large study reported that active or recent chemotherapy was not a predictor of severe disease, whereas checkpoint inhibitor therapy and age over 65 years were associated with adverse outcomes [1]. Here we describe the outcomes of three consecutive patients with myeloma and concurrent COVID-19 infection admitted at our tertiary care centre between April and June 2020, whilst on lenalidomide-based therapy, two of whom underwent autologous stem cell transplant, with at least 30 days of follow-up.